2023
DOI: 10.1038/s41598-023-28412-7
|View full text |Cite
|
Sign up to set email alerts
|

A proteome scale study reveals how plastic surfaces and agitation promote protein aggregation

Abstract: Protein aggregation in biotherapeutics can reduce their activity and effectiveness. It may also promote immune reactions responsible for severe adverse effects. The impact of plastic materials on protein destabilization is not totally understood. Here, we propose to deconvolve the effects of material surface, air/liquid interface, and agitation to decipher their respective role in protein destabilization and aggregation. We analyzed the effect of polypropylene, TEFLON, glass and LOBIND surfaces on the stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Protein aggregation occurred due to the high shear experienced by the substrate and the high concentration of adsorbed proteins due to the high density of amino groups in the Ti-TMS-PEI. Our results are also consistent with the study of Schvartz et al [ 22 ] on the effect of agitation on protein aggregation and the work of Borzova et al [ 23 ] on the thermal denaturation and aggregation of BSA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Protein aggregation occurred due to the high shear experienced by the substrate and the high concentration of adsorbed proteins due to the high density of amino groups in the Ti-TMS-PEI. Our results are also consistent with the study of Schvartz et al [ 22 ] on the effect of agitation on protein aggregation and the work of Borzova et al [ 23 ] on the thermal denaturation and aggregation of BSA.…”
Section: Discussionsupporting
confidence: 93%
“…Another hypothesis for the cause of the positive effects of the amino-rich organic layers is the increased adsorption of serum proteins such as vitronectin or fibronectin and the resulting enhanced interaction of cellular integrin receptors with the coated surface [ 19 , 20 ]. Several studies reported that amino-functionalized surfaces also have a high adsorption capacity of bovine serum albumin (BSA) due to the protein’s high stability and varying surface charges under neutral or acidic conditions [ 21 , 22 , 23 ]. These proteins adsorbed on the surface are essential in the subsequent interaction of an implant with cells, and the protein density on the surface dictates how cells would behave, such as how they would spread or migrate on the surface [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%